Intake of isoflavone-supplemented soy yogurt fermented with Enterococcus faecium lowers serum total cholesterol and non-HDL cholesterol of hypercholesterolemic rats - Rossi, Elizeu Antonio [UNESP]; Cavallini, Daniela Cardoso Umbelino [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Vendramini, Regina Célia [UNESP]; Damaso, Ana Raimunda; de Valdez, Graciela Font (Springer, 2008)
The aim of this study was to obtain an isoflavone-supplemented soy yogurt, fermented with Enterococcus faecium CRL 183 and Lactobacillus helveticus ssp jugurti, with suitable sensory properties and to assess the effects of the final product on blood lipids in hypercholesterolemic rats. Four isoflavone supplementation procedures were tested, in which the isoflavone was added at these stages: (1) before heat-treatment; (2) after heating and before fermentation; (3) after fermentation and (4) in the okara (by-product of soy milk) flour stirred into the fermented product when consumed. The products were subjected to a test of sensory acceptability. To assess their potential hypocholesterolemic properties in vivo, four groups of rats were used: control (C), hypercholesterolemic (H), hypercholesterolemic plus fermented product (HF) and hypercholesterolemic plus isoflavone-supplemented fermented product (HFI). Hypercholesterolemia was induced in rats of groups H, HF and HFI by feeding them on a commercial rat chow to which cholesterol and cholic acid had been added. Total, HDL and non-HDL cholesterol and triglycerides were measured in the blood of the rats. No significant sensorial differences were detected among the samples of soy yogurt supplemented with isoflavones at various processing stages. Rats fed a fermented soy product enriched with isoflavones (HFI group) had significantly (P < 0.05) less serum total cholesterol (15.5%) compared with rats fed a hypercholesterolemic diet (H group). Non-HDL cholesterol was less (P < 0.05) in rats fed a fermented soy product enriched or not with isoflavones (27.4 and 23.2%) compared to H group. The HDL-C and triglyceride concentrations did not differ significantly among the groups. It was possible to obtain an isoflavone-supplemented soy yogurt with satisfactory sensory characteristics. The resulting supplemented soy yogurt was capable of producing a lipid-lowering effect in hypercholesterolemic rats, relative to the animals that did not consume this product.
Keywords: Soy yogurt; Isoflavones; Lipid-lowering effects; Probiotic; Rats